Bacteria Assemble: Investigating Soil Bacterial Diversity and Interactions in a Sarawakian Oil Palm Plantation for Climate-Resilient Soil Management - Zahidah Ayob; Nor Azizah Kusai; Han Ming Gan; Wan Nurul‘Ain Wan Mohd Nor; Hasimah Mos; Vijaya Subramaniam; Meilina Ong Abdullah (E3S Web of Conferences)
Investigating bacterial diversity in the soil of oil palm plantations is crucial for developing effective soil management strategies to mitigate greenhouse gas emissions, thereby addressing climate change challenges. In this study, we analysed soil bacterial communities within an oil palm plantation in Sarawak, Malaysia. To capture the full spectrum of microbial diversity, samples were collected across three distinct soil depths and various managements zones within the plantation. We employed Illumina amplicon sequencing targeting the V3 region of the 16S rRNA gene, which revealed a diverse array of soil bacteria, primarily from the phyla Acidobacteriota, Actinobacteriota, and Proteobacteria. Notably, families such as RAAP2_2 and Isosphaeraceae were identified as key biomarkers predominantly inhabiting deeper soil layers (30-45 cm), while UBA7541, Streptosporangiaceae, and Sporichthyaceae were more prevalent in the surface layer (0-15 cm). Microbial correlation network analysis revealed a complex network of robust and significant interactions among 11 bacterial families, suggesting their involvement in plant material degradation and carbon cycling. Redundancy Analysis (RDA) revealed that pH, moisture content, and bulk density were significant factors that influence the microbial community structure. At the phylum level, Acidobacteriota showed a close association with pH, while Proteobacteria was associated with higher moisture content. Interestingly, we discovered that the soil was not as homogeneous as initially thought. Microenvironmental variability was evident, with specific groupings based on subplot sampled. These findings provide valuable insights into the factors shaping microbial communities in oil palm plantation soils, thus opening avenues for further exploration of the complex mechanisms driving ecosystem processes in this unique Malaysian soil environment.